2015
DOI: 10.1183/13993003.01196-2014
|View full text |Cite
|
Sign up to set email alerts
|

Novel concepts in airway inflammation and remodelling in asthma

Abstract: The hallmark pathological features of asthma include airway eosinophilic inflammation and structural changes (remodelling) which are associated with an irreversible loss in lung function that tracks from childhood to adulthood. In parallel with changes in function, pathological abnormalities occur early, during the pre-school years, are established by school age and subsequently remain (even though symptoms may remit for periods during adulthood). Given the equal importance of inflammation and remodelling in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 84 publications
4
120
0
3
Order By: Relevance
“…41 Individuals with severe asthma have increased tissue remodelling, compared to individuals with mild-to-moderate disease. [42][43][44] However, most animal models only assess acute lung inflammation and tissue responses over a relatively short time period.…”
Section: Chronic Inflammation and Tissue Remodellingmentioning
confidence: 99%
“…41 Individuals with severe asthma have increased tissue remodelling, compared to individuals with mild-to-moderate disease. [42][43][44] However, most animal models only assess acute lung inflammation and tissue responses over a relatively short time period.…”
Section: Chronic Inflammation and Tissue Remodellingmentioning
confidence: 99%
“…In this review, we were invited to highlight experiments conducted primarily in our laboratories (in conjunction with many collaborators) that have focused on understanding the fundamental pathways underpinning the pathogenesis of asthma by employing a range of mouse models (see for excellent reviews with broader field focus). In the development of these models, we have utilized the clinical data of the “time” to shape the development of appropriate models to gain insights into pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicated that asthma is caused by an inheritable epigenetic event which modifies protein expression [11,34]; thus, post-transcriptional control became focus of interest. Reflecting these new data on epigenetic events and airway wall remodelling in asthma, the American Thoracic Society stated that unless airway wall remodelling is understood, there will be no cure for asthma [4]. Thus, the search for new therapeutic targets in asthma has to be promoted.…”
Section: Epigenetics Translation and Remodellingmentioning
confidence: 99%
“…Earlier it was thought that airway wall remodelling results from term chronic inflammation in asthma or COPD [1][2][3][4]. Recent clinical studies indicated that airway wall remodelling occurs before or without inflammation [1,5,6].…”
Section: Introductionmentioning
confidence: 99%